The time series at the Strait of Gibraltar as a baseline for long-term assessment of vulnerability of calcifiers to ocean acidification - Amaya-Vías, Silvia; Flecha, Susana; Pérez, Fiz F.; Navarro, Gabriel; García-Lafuente, Jesús; Makaoui, Ahmed; Huertas, I. Emma (Frontiers in Marine Science, 2023)
The assessment of the saturation state (Ω) for calcium carbonate minerals (aragonite and calcite) in the ocean is important to determine if calcifying organisms have favourable or unfavourable conditions to synthesize their carbonated structures. This parameter is largely affected by ocean acidification, as the decline in seawater pH causes a decrease in carbonate ion concentration, which in turn, lowers Ω. This work examines temporal trends of seawater pH, ΩAragonite and ΩCalcite in major Atlantic and Mediterranean water masses that exchange in the Strait of Gibraltar: North Atlantic Central Water (NACW), Levantine Intermediate Water (LIW) and Western Mediterranean Deep Water (WMDW) using accurate measurements of carbonate system parameters collected in the area from 2005-2021. Our analysis evidences a gradual reduction in pH in the three water mases during the monitoring period, which is accompanied by a decline in Ω for both minerals. The highest and lowest decreasing trends were found in the NACW and LIW, respectively. Projected long-term changes of Ω for future increases in atmospheric CO2 under the IPCC AR6 Shared Socio-economic Pathway "fossil-fuel-rich development" (SSP5-8.5) indicate that critical conditions for calcifiers with respect to aragonite availability will be reached in the entire water column of the region before the end of the current century, with a corrosive environment (undersaturation of carbonate) expected after 2100.